"The Talk" regarding minority youth interactions with police. Issue 4 (2nd October 2019) - Cintron, Myrna; Dawkins, Marika; Gibson, Camille; Hill, Milton C.
Abstract: This mixed methods descriptive study is an effort to describe whether "The Talk" (regarding behavior during interactions with police) occurs equally in African American, Latino, and White families and to determine the content of these conversations. A sample of 307 university students, in three areas of Texas, were surveyed with closed and open-ended items. Data were analyzed quantitatively using descriptive statistics and t-test difference between proportion analyses and qualitatively through a process of coding to identify patterns and themes in the open-ended responses. The findings reveal that a majority (74%) of the youth surveyed have had "The Talk" with their parents/guardians, and this influences their perceptions of the police. Unsurprisingly, African Americans were found to be more fearful and distrustful of law enforcement than Whites and Latinos. Latinos shared many similar, more positive, perceptions of law enforcement with Whites in contrast to African Americans. Whites, however, evidenced the most faith in law enforcement and in the idea that their complaints about police misconduct would attain results.